Cost Benefit Analysis of Energy Retrofitting with the Addition of Ventilation Holes in Middle Low-Income Houshold Buildings - Elvarettano, Rhesa Akbar; Hamidah, Nur Laila; Aulady, Mohamad Ferdaus Noor (Jurnal IPTEK, 2024)
The current climate change is characterized by an increase in the earth's surface temperature; one of the impacts that is felt quite significantly is the thermal comfort conditions in buildings. This will encourage residents to use air conditioning to provide the required level of thermal comfort. From the results of electricity demand forecasts, from 2017 to 2036, electricity demand will increase by 6.4% annually, dominated by the household sector at 38.49%. Efforts can be made to condition the room's thermal comfort to reduce the AC's operating time. This can be realized through building energy retrofitting, especially in middle-low-income households. Retrofitting will also not require high costs, so it suits middle-low-income households. In this research, retrofitting was carried out by implementing ventilation. It is hoped that ventilation will naturally provide air to specific rooms through air movement and exchange. This study implemented 12 variations in ventilation, namely variations with cross ventilation and non-cross ventilation, then varied the size of the ventilation and the number of ventilations. This research was carried out based on simulations using Computational Fluid Dynamics. After carrying out the simulation, it was obtained that the most significant decrease in indoor temperature was when cross ventilation was applied at night with ventilation measuring 30 cm x 70 cm with a total of 4 vents, namely with a decrease in the average indoor temperature of 1.614C. After that, a cost-benefit analysis was carried out to compare the costs and benefits of a project; a cost-benefit ratio of 1.26 was obtained, where the profits were more significant than the expenditure costs, a payback period value of 0.402 was obtained, or the capital could be returned for five months, and savings were obtained. Electricity consumption costs up to year five amount to IDR 24,340,306.